The Performance of Women's Empowerment in Moringa Processing Using the CIPP Model Evaluation - Herwina, Wiwin; Karwati, Lilis; Sundari, Ristina Siti (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2025)
Moringa processing contributes significantly to public health, sustainable agriculture, and food security. This study evaluated the women's empowerment program implemented by KWT Roay Lestari in Tasikmalaya City using the Context–Input–Process–Product (CIPP) framework and a mixed-methods approach. Key informants—program leaders, members, and consumers—were selected through purposive sampling. Data were collected through observation, structured interviews, and documentation, and analyzed using OriginLab 2024, IBM SPSS Statistics 25, and Statistics 8.1. The findings reveal that the program had a positive influence on women's educational awareness, economic conditions, and household food security. Despite financial and time constraints, participants demonstrated a strong commitment to skill development and social interaction. Increased female participation enhanced technical skills, raised income levels, and expanded the use of moringa-based products in local diets. Growing consumer trust and demand further indicate the program's effectiveness. However, limited infrastructure, particularly the lack of adequate storage and grinding equipment, remains a significant challenge. While training has improved product quality and encouraged creativity, further innovation in food preservation is needed to ensure long-term market sustainability. Overall, the program demonstrates strong relevance and impact in promoting agricultural development and women's economic empowerment. Strengthening training, infrastructure, stakeholder collaboration, and investment in processing technology is essential for sustainable growth and scalability